STUDY AND MODIFICATION OF SOOT BLOWER IN SUGAR INDUSTRY - PROF. KARE K.M.; TAMBE PRATIK PRAMOD; PAWAR RAMDAS BALASO (International Journal of Innovations in Engineering Research and Technology, 2021)
Due to the unbalancing of the impeller of soot blower the vibrations are generated which causes the damage to the soot blower and get breakdown after some time period of working.